2014
DOI: 10.3126/ajms.v5i4.8724
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive dysfunction among HIV positive patients using International HIV dementia scale

Abstract: Background: HIV associated neurocognitive dysfunction (HAND) ranges from asymptomatic neurocognitive impairment (ANI) to mild neurocognitive disorders (MND) to HIV associated dementia (HAD). Cognitive impairment may impact medication adherence which will ultimately affect morbidity and mortality. Aim: This study was undertaken to evaluate neurocognitive dysfunction among HIV positive patients using the International HIV Dementia scale(IHDS). Materials and Methods: This cross sectional study was conducted in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 17 publications
0
26
2
Order By: Relevance
“…As compared to prior studies, the current finding is similar with the result of a study conducted in India (32.5%) (18), a study done in Nigeria (34.4%) [28] and an earlier Metaanalysis (systemic review) in Sub-Saharan area (30.9%) (2). However, it is less than the findings of previous studies undertaken in Botswana (38%) (21), a study in the international community (37%) (15), a study done in Cameroon (85%) [29], a study conducted in Asia (90%) (19) and a Ugandan study (46.49%) (30,31,32). …”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…As compared to prior studies, the current finding is similar with the result of a study conducted in India (32.5%) (18), a study done in Nigeria (34.4%) [28] and an earlier Metaanalysis (systemic review) in Sub-Saharan area (30.9%) (2). However, it is less than the findings of previous studies undertaken in Botswana (38%) (21), a study in the international community (37%) (15), a study done in Cameroon (85%) [29], a study conducted in Asia (90%) (19) and a Ugandan study (46.49%) (30,31,32). …”
Section: Discussionmentioning
confidence: 78%
“…The problem of NCD in sub-Saharan area ranges from 20% – 37% as reported in prior studies (2,11,13). A report in the multi-center international studies that were conducted in Thailand, Zaire, Kenya, Brazil and Germany revealed that the neuropsychological deficit among HIV-positive people ranged from 13% in Brazil to 19% in Zaire (14,15,16).…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations